EJMM 2021
DOI: 10.51429/ejmm30113
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Biofilm and Siderophore Encoding Genes Implicated in the Pathogenesis of Klebsiella pneumoniae Isolated from Different Clinical Specimens

Abstract: Background: Biofilm and siderophores protect K. pneumoniae, making them resistant to antimicrobials and increase the ability to evade immune system. Objective: The aim of the present study was to detect some of the virulence genes responsible for biofilm formation and siderophore production implicated in the pathogenesis of K. pneumoniae. Methodology: Crystal violet method was used to detect biofilm phenotypically, hypermucoviscosity by string test and virulence genes were detected by PCR. Results: Phenotypica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
1
Order By: Relevance
“…The Klebsiella pneumoniae isolates producing siderophore was 73.33% is our study results, (Siderophore production is more from endotracheal & pus samples in our study). This is in contrast to other studies which reported 100% in -Aljanaby et al 31,34 It has been shown that the development of invasive forms of the disease is associated with the production of several siderophores by K. pneumoniae strains. Hv-KP strains produce more siderophore molecules and in their more active form, than c-KP.…”
Section: Discussioncontrasting
confidence: 71%
“…The Klebsiella pneumoniae isolates producing siderophore was 73.33% is our study results, (Siderophore production is more from endotracheal & pus samples in our study). This is in contrast to other studies which reported 100% in -Aljanaby et al 31,34 It has been shown that the development of invasive forms of the disease is associated with the production of several siderophores by K. pneumoniae strains. Hv-KP strains produce more siderophore molecules and in their more active form, than c-KP.…”
Section: Discussioncontrasting
confidence: 71%